Distribution, Drivers, and Threats of Aluminum in Groundwater in Nova Scotia, Canada - Kristin A. Hart; Gavin W. Kennedy; Shannon M. Sterling (Water, 2021)
Increased rates of acid deposition derived from the burning of fossil fuels over the last century have resulted in the acidification and increase in aluminum (Al) levels in freshwaters and soils in sensitive areas. While the acidification of surface waters such as lakes and rivers has been extensively studied, the acidification status and resulting Al concentrations in groundwater are poorly understood. Here we aim to describe the distribution of Al in groundwater across the province of Nova Scotia, Canada. We investigate the hydrogeological conditions that influence Al concentrations in groundwater and compare Al concentrations to legislated threshold levels for human and aquatic health. We found groundwater Al concentrations to be highest in areas underlain by plutonic and metamorphic bedrock types as well as surficial aquifers, with pH and organic carbon concentrations having the strongest correlation with groundwater Al concentrations. Few samples exceed the maximum acceptable concentration of 2900 µg/L released by Health Canada (2021), but these exceedances are important to highlight given the challenges with respect to Al treatment in private domestic wells and our evolving understanding of Al impacts to human health. High concentrations of Al in groundwater may also be exported to surface waters such as rivers and lakes, where they can be harmful to aquatic populations such as Atlantic salmon (Salmo salar). We recommend that private well owners test their water supplies for Al, and that further studies on Al export from groundwater to surface water be carried out in the most high-risk areas coincident with important Atlantic salmon river watersheds.